2016
DOI: 10.1016/j.ijheatfluidflow.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of a self-similar adverse pressure gradient turbulent boundary layer

Abstract: The statistical scaling properties of a self-similar adverse pressure gradient (APG) turbulent boundary layer (TBL) are presented. The intended flow is generated using the direct numerical simulation (DNS) TBL code of Simens et al. (2009) and Borrell et al. (2013), with a modified farfield boundary condition (BC). The conditions for self-similarity and appropriate scaling are derived, with mean and Reynolds stress profiles presented using this scaling. The APG and ZPG DNS are also compared under the classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 34 publications
(18 reference statements)
6
73
2
Order By: Relevance
“…Also note that the value of U + is not constant for in the APG TBL, contrary to what is observed in ZPG TBLs. This has been documented among others by Kitsios et al [37], and leads to problems in the determination of the boundary-layer thickness as discussed by Vinuesa et al [54]. On the other hand, note that the mean velocity profile at x s s / c = 0.4 was also reported by Hosseini et al [1], as part of a comparison between suction and pressure sides at matched R e τ values.…”
Section: Turbulence Statisticsmentioning
confidence: 61%
“…Also note that the value of U + is not constant for in the APG TBL, contrary to what is observed in ZPG TBLs. This has been documented among others by Kitsios et al [37], and leads to problems in the determination of the boundary-layer thickness as discussed by Vinuesa et al [54]. On the other hand, note that the mean velocity profile at x s s / c = 0.4 was also reported by Hosseini et al [1], as part of a comparison between suction and pressure sides at matched R e τ values.…”
Section: Turbulence Statisticsmentioning
confidence: 61%
“…Note that the logarithmic skin-friction relation and its low- R e correction have found widespread preference compared to other empirical relations since the early work by Rotta [41]. The values of the various coefficients in the correlations (1) and (2) used in the present work for the ZPG, and the APG cases with constant β = 1 (including Kitsios et al [25]) and 2, are given in Table 3. In order to obtain the various coefficients, the data with R e 𝜃 > 2000 was first fit to Eq.…”
Section: Criteria To Identify “Well-behaved” Apg Tblsmentioning
confidence: 93%
“…Figure 1 (bottom) includes, for reference, the Reynolds-number evolution of the Clauser pressure-gradient parameter of the five databases from the literature listed in Table 2. Note that in the two databases containing regions of constant β , namely the ones by Kitsios et al [25] and Lee [26], only the β values from the profiles analyzed here are shown.
Fig.
…”
Section: Description Of the Databases Analyzed In The Present Studymentioning
confidence: 99%
See 2 more Smart Citations